(untitled) (Annals of Medical Research, 2021)
Cancer cells utilize glucose quite differently from regular cells as cancer cells metabolize glucose more in aerobic glycolysis rather than in oxidative phosphorylation. Whereas aerobic glycolysis is less effective in the metabolism than oxidative phosphorylation. This review aims to explain the mechanisms of cancer metabolism and recent findings related to the subject. There are excessive glycolysis and glucose transport in tumor cells, this situation as known Warburg effect. Mitochondrial impairment, hypoxia, oncogenic signals, and defected metabolic enzymes are mechanisms of this cancer metabolism. Results of increased glycolysis are quick production of ATP and intermediates for biosynthetic pathways and occur acidic cell environment. The oncogenes, hypoxia-inducible factor (HIF), serine/threonine kinase Akt, K-ras, c-myc, AMP-activated protein kinase (AMPK) and p53 have important roles in cancer metabolism. HIF, Akt, K-ras, c-myc, AMPK, and p53 are important oncogenes in cancer metabolism. The differences in metabolism of cancer cells are important targets for new treatment methods.